A short note about the editions of the Parini’s ode “A Silvia” (Prassi Ecdotiche della Modernità Letteraria, 2016)
The most authoritative text of the Parini’s ode A Silvia has been identified by Dante Isella, confimed by Franco Longoni and Mirella D’Ettorre. It is an opuscule whose text is considered more correct than the one published in Como, considered the editio princeps. The two opuscules are typographically similar, although published by different printers: the first one has probably been printed by the same printer of the ode Alla Musa, now archived in Ambrosiana Library (Milan).
Keywords: Parini; A Silvia; Odi; Dante Isella; editio princeps; first edition